Vietnam legal corridor for protection of payment to contractor - Duong, Vuong Thi Thuy; Thiem, Tran Thi (Journal of Transportation Science and Technology, 2022)
According to the General Statistic Office of Vietnam, the construction industry has continued to grow relatively in 2020 with a value-add of 6.76% despite of impact of the COVID-19 pandemic. The Vietnam construction market incorporates almost small and medium enterprises and has had lots of payment disputes related to lawsuit. This study aims not only to examine the definition of payment to contractor in investment construction operations but also to outline existed legal corridor promulgated to secure the contractor’s payment. Using the systematic analyzing method of previous researches, some types of Vietnam legal documents and other countries to determine what the payment to contractor is and how it is safeguarded by legal corridor in Vietnam. As a result, under Vietnam legal documents, although the regulations on protection of payment to contractor have been mentioned, they are not enough legal deterrence to restrict the payment terms and conditions breaches in the construction contract.